From Diagnosis to Therapy: A Comprehensive Review on the Role of Radioactive Isotopes in Thyroid Cancer Management - Rasheed, Zahraa A.; Ayyed, Hawraa K.; Raheem, Zeena J.; Al-Salmani, Tebarak A.A. (Journal of Pharmacology and Drug Development, 2025)
The use of radioactive isotopes in the diagnosis and treatment of thyroid cancer is now an integral part of modern nuclear medicine. Gamma-emitting isotopes such as technetium-99m and iodine-123 serve as the main diagnostic imaging weapon enabling great sensitivity and specificity, non-invasive functional visualization of thyroid physiology and disease. Todine-131 is the dominant therapeutic isotope, emitting cytotoxic beta radiation for the treatment of metastatic differentiated thyroid cancer and thyroid remnant ablation. The effectiveness of radioactive iodine treatment is dependent on various factors including sodium-iodide symporter expression as well as dosimetry methods seeking to maximize absorbed dosages whilst simultaneously achieving successful treatment alongside minimizing non-target organ toxicity. Molecular radiotheragnostics and personalized dosimetry methods are slowly entering the clinical routine and will ensure higher diagnostic power and treatment efficacy in the future. Radioiodine-refractory thyroid cancers have long been challenging to manage, warranting novel approaches to integrate molecular biology, targeted therapies and immunotherapy.The changing context of radionuclide use in thyroid care highlights the necessity of multidisciplinary approaches, which promise to increase patient outcomes and the management of thyroid cancer